Implementation of Automation on Employee Rights in Termination of Employment - Wardah, Kurniaty; Hoesin, Siti Hajati (Syntax Literate, 2025)
The implementation of technological advancements has significantly impacted the labour sector, particularly in employment relations. Automation enhances efficiency and productivity, leading to job termination (layoffs) for affected workers. This study analyzes the impact of automation on employment relations and the fulfillment of workers' rights after layoffs in Indonesia and Malaysia. The research method used is normative juridical research, utilizing secondary data and case studies. The findings indicate that although labour regulations in Indonesia govern the mechanisms of employment termination and workers' rights, practical implementation still faces challenges. The case study of PT Jasa Marga (Persero) Tbk in 2017 demonstrates the company's commitment to justice and employee welfare by avoiding forced layoffs and instead providing a career transition program. In contrast, the case of layoffs conducted by TikTok in Malaysia in 2024 highlights the lack of worker protection, lower compensation, and minimal transition programs. This comparison shows that PT Jasa Marga in Indonesia prioritizes worker protection through dialogue and transition policies, whereas the Malaysian case emphasizes efficiency over worker welfare. Therefore, more adaptive labour policies are needed to balance industrial efficiency and workers' rights protection in response to technological advancements.